2010
DOI: 10.1088/0957-4484/21/38/385704
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid templated porous nano-TiO2particles for the selective isolation of cytochrome c

Abstract: Porous nano-titanium dioxide (TiO(2)) particles with anatase framework were prepared by using an effective template of hydrophobic ionic liquid, i.e., N, N-bis [2-methylbutyl] imidazolium hexafluorophosphate ([PPim][PF(6)]). The nano-TiO(2) particles were characterized with TEM and BET, resulting in the distribution of the pore diameters centering at 7.3 nm and 26.2 nm, attributed to the template effect of the ionic liquid and the aggregation of the TiO(2) particles, respectively. A much improved surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…However, dipolar interactions were suggested to change the effective anisotropy of the particles [ 92 ]. In addition, the applied magnetic field strength should be in the linear region of the Langevin curve [ 93 ].…”
Section: The Role Of Inter-particle Interactions On the Heating Efmentioning
confidence: 99%
“…However, dipolar interactions were suggested to change the effective anisotropy of the particles [ 92 ]. In addition, the applied magnetic field strength should be in the linear region of the Langevin curve [ 93 ].…”
Section: The Role Of Inter-particle Interactions On the Heating Efmentioning
confidence: 99%
“…The Atomic Force Microscope (AFM) is a typical surface imaging instrument for micro- or nano-scale specimens. More recently, researchers have adopted it to measure force down to picoNewton (pN) scale in biophysics and nanomechanical fields [ 1 , 2 ]. Such applications need to measure or control the force between the force sensor (the AFM cantilever probe) and the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…Porous nano-titanium dioxide particles with anatase framework and crystallite sizes of approximately 15 [28]. Farag et al [29] reported the synthesis of titania in the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide (Py14TFSA) via sol-gel method, the nanopowder being characterized by a high thermal stability and BET surface area of 97 m 2 g −1 .…”
Section: Introductionmentioning
confidence: 99%